PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PEMBELAJARAN MEMBACA PEMAHAMAN MELALUI MODEL PROBLEM BASED LEARNING (PBL), KOMBINASI THINK PAIR SHARE (TPS) DAN TALKING STICK DI KELAS IV SDN SUNGAI MIAI 4 BANJARMASIN - Imelda Rosiana; Mahmuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study seeks to enhance critical thinking and reading comprehension skills in students by implementing the Problem-Based Learning (PBL) paradigm in conjunction with Think Pair Share (TPS) and Talking Stick methodologies. The issue encountered is the inadequate critical thinking and reading comprehension abilities of fourth-grade pupils at SDN Sungai Miai 4 Banjarmasin, attributable to traditional and less engaging instructional methods. This research employed a Classroom Action Research (CAR) methodology executed across four cycles, with 19 students as participants. The data gathering methods comprised the observation of instructor and student activities, critical thinking skill assessments, and evaluations of learning outcomes. The results demonstrate that the regular implementation of the three learning models enhances the quality of learning. Teacher and student activities demonstrated a considerable enhancement from the